“Wait, is she Black?”: Unsuccessful White Pass in Tiffany D. Jackson’s The Weight of Blood - Myllymäki, Monica; Ghasemi, Mehdi (SAGE Publications, 2026)
In this article, we study Tiffany D. Jackson’s novel The Weight of Blood (2022) as a neo-passing narrative that interrogates the colour-blind ideology and the idea of a post-racial society. By focussing on the biracial character of Maddy Washington, we explore the necessity of white passing in contemporary American society and examine her challenges after her unsuccessful attempt at passing. We aim to show that, despite the false claims of post-racialism, racial predicaments are still intact in American society in the 21st century. To offer a better analysis of the novel, we draw upon W.E.B. Du Bois’s notions of the “colour-line” and “double consciousness.” Du Bois’s theories enable us to further explore the black-white racial hierarchies and dichotomies, as well as the persistence of colour-blindness within today’s American society.